Igreja Pentecostal Deus é amor: origens, características e expansão - Mendonça, Emilio Zambon (2009)
Interpretation Masters dissertation; We seek to demonstrate that the Pentecostal Church "God is Love" - ​​IPDA is a Church, expanding in the last five decades. Our Master's Dissertation indicates that IPDA has elected the radio media, its newspaper and its own magazines to publicize its activities. The study demonstrates that the IPDA is alien to politics, does not interview other radio stations, prohibits television use, and does not serve journalists or researchers. Based on our 11-year experience at the Pentecostal Church "God is Love," including For five years as a deacon, we have rescued details that will provide input to scholars and researchers of current Pentecostal phenomena. By covering some space not yet researched by the academy, we complement, on the other hand, data that are not in the autobiography of David Martins de Miranda, founder of IPDA. Finally, we seek to identify doctrinal characteristics of the IPDA and its administrative processes, which denote a certain tendency toward professionalization by the board's staff in the succession process. We also address the issue of the institution's reproduction, which has hitherto been kept under the charisma of its founder who has been running his church with all the characteristics of a family business, within a sect / church gradient. Our findings demonstrate the strategies that enabled the expansion of IPDA based on its radios, high concentrations, proselytizing appeal and fundraising, factors that nourish and support the growth of the Pentecostal Church "God is Love." ) On pp. 69-77, point 2.2 deals with "Rites and Interpretation of the Bible" baptism - marriage - forbidden beard - anointing with oil - holy supper